Concurrent Validity of Actigraph-Determined Sedentary Time Against the Activpal Under Free-Living Conditions in a Sample of Bus Drivers. Issue 4 (2nd October 2017) - Varela Mato, Veronica; Yates, Thomas; Stensel, David; Biddle, Stuart; Clemes, Stacy A.
ABSTRACT: This study explored the validity of ActiGraph-determined sedentary time (<50 cpm, <100 cpm, <150 cpm, <200 cpm, <250 cpm) compared with the activPAL in a free-living sample of bus drivers. Twenty-eight participants were recruited between November 2013 and February 2014. Participants wore an activPAL3 and ActiGraph GT3X+ concurrently for 7 days and completed a daily diary. Time spent sedentary during waking hours on workdays, non-workdays, during working-hours, and non-working hours were compared between instruments. During working hours, all ActiGraph cut-points significantly underestimated sedentary time ( p  < 0.05), whereas during non-working hours the <50 cpm cut-point demonstrated the closest agreement (ActiGraph sedentary time: 250 ± 75 minutes versus activPAL sedentary time: 236 ± 65 minutes). Receiver operating characteristic analyses revealed that on workdays and non-workdays the ActiGraph cut-points exhibited relatively low sensitivity (all <0.62) and specificity (all <0.49) values. The use of the ActiGraph to measure sedentary time in this understudied, highly sedentary and at risk occupational group is not recommended.